Host resistance in cattle to infestation with the cattle tick Rhipicephalus microplus. (30th October 2014) - Jonsson, N. N.; Piper, E. K.; Constantinoiu, C. C.
Summary: Resistance to Rhipicephalus microplus infestation in cattle has many effector mechanisms, each of which is likely to be modulated by complex, interacting factors. Some of the mechanisms of host resistance and their modulating factors have been identified and quantified, although much remains to be explained. The variation in resistance to tick infestation is most marked between Bos taurus and Bos indicus cattle, taurine cattle given the same exposure carrying between five and 10 times as many ticks as indicine cattle. Tick resistance is mostly manifest against attaching larvae, which attempt to feed often and without success, death occurring mostly within 24 h of finding a host. There is evidence of innate and adaptive immune response to tick infestation, and it appears that the relative importance of each differs between indicine and taurine cattle. There is conflicting information regarding the role of humoral immunity in tick resistance, and recent studies indicate that strong IgG responses to tick antigens are not protective. A strong T‐cell‐mediated response directed against larval stages, as mounted by indicine cattle, seems to be protective. Variation in the extracellular matrix of skin (epidermal growth factors, collagens and other matrix components such as lumican) also contributes to variation in host resistance.